[PP.34.36]: MILD COGNITIVE IMPAIRMENT OF VASCULAR GENESIS. (June 2015) - Bezzubik>, E.>; Vartanov, A.; Popov, V.; Menenkova, E.; Isakova, J.
Abstract : Objective: Hypertension, that could cause cerebrovascular insufficiency and lead to cognitive decline, is one of the most common vascular disease for locomotive drivers. The demands to their health are very strict. That's why they almost never express complaints. At the same time impairment of attention, memory or thinking could affect professionally significant functions of operators. Even mild cognitive impairment is very dangerous for professional drivers and present additional risk factor for safe duties performing. Unfortunately current available methods of regular examinations of operators are considered to be not sensitive enough to detect mild cognitive disorders. Design and method: We searched for research papers reporting original and epidemiological studies results on early diagnostics of mild cognitive impairment. In our work we used such sources as Pubmed, Medline Cochrane databases. Results: We prepared neuropsychological testing battery considered to be sensitive enough to detect mild cognitive impairment in middle-aged population. In our battery we included tests for evaluation of every cognitive domain. By now we examined 10 patients with mild cerebrovascular insufficiency, locomotive drivers, 27–54 years old. 2 of them are hypertensive's. All of them had no cognitive complaints. However test results showed that 5 out of 10, including patients with hypertension, had initial symptoms of cognitive impairment such as slowness of thinking and concentration difficulty. Conclusions: Early diagnostics of mild cognitive impairment is especially important for locomotive drivers, because cognitive decline could impact their professionally significant functions and lead to dangerous errors. Drivers with hypertension should be diagnosed first, because they have higher risk of early cognitive dysfunction. Mild cognitive impairment can be diagnosed by using neuropsychological battery, if it will be composed in a right way and will contain sensitive test for every cognitive domain with special interpretation paths. The research should be continued to collect more data and to make a convincing conclusion on appropriate neuropsychological methods of early detection of mild cognitive impairment.